2005
DOI: 10.1016/s0377-1237(05)80011-5
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Multi-drug Resistant Salmonella Typhi Enteric Fever in Mumbai Garrison

Abstract: Background: There was an epidemic of enteric fever in Mumbai garrison during Nov-Dec 2000 with more than 150 cases admitted to a tertiary care service hospital. Methods: All the cases presented with fever and some had splenomegaly, bradycardia, abdominal pain and diarrhoea. The epidemic was investigated by the station health organization (SHO) and the case and bacteriological study was carried out in pathology laboratory of the service hospital. The serological study was carried out at Armed Forces Medical Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 5 publications
3
10
1
Order By: Relevance
“…chloramphenicol, cotrimoxazole, and ampicillin, was noted in 79.1% of S. enterica serotype typhi/paratyphi in present study. The results are comparable to previous studies which have reported 80-90% (Hatta 2008) and100% (Misra 2005). The increased drug resistance results from the exploitation of drug use by chemist, druggist, quacks, and paramedics and more over by patients himself as self medication.…”
Section: Discussionsupporting
confidence: 86%
“…chloramphenicol, cotrimoxazole, and ampicillin, was noted in 79.1% of S. enterica serotype typhi/paratyphi in present study. The results are comparable to previous studies which have reported 80-90% (Hatta 2008) and100% (Misra 2005). The increased drug resistance results from the exploitation of drug use by chemist, druggist, quacks, and paramedics and more over by patients himself as self medication.…”
Section: Discussionsupporting
confidence: 86%
“…These include -high degree of resistance to chloramphenicol (56.6%), ampicillin (40%), amikacin (50%), gentamicin (43.3%), ampicillin (40%), cotrimoxazole (33.3%), and cephalexin 30% with very low resistance to ceftriaxone and cefotaxime (6.6% each), and 100% sensitivity to ciprofloxacin, from Rajasthan [6], resistance to chloramphenicol and sensitivity to ciprofloxacin from Mumbai [7], 80% of isolates showing resistance to amoxicillin, chloramphenicol and cotrimoxazole along with 100% sensitivity to ciprofloxacin and ceftriaxone from Ahmedabad [8], and high resistance to amoxicillin, chloramphenicol, ampicillin, co-trimoxazole and ciprofloxacin from Mangalore [9]. Amidst these, there have been reports of reemergence of sensitivity in Salmonella enterica serovar typhi to chloramphenicol and other first line drugs [4,[10][11][12][13], giving us a reason to analyse and report our data.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from different parts of India have reported the development of resistance of S. Typhi to various antibiotics [7,8]. In the central west parts of India, fluoroquinolones and third-generation cephalosporins are the mainstay of treatment for typhoid fever [9,10].…”
Section: Introductionmentioning
confidence: 99%